2003
DOI: 10.1002/mus.10359
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab in the treatment of polyneuropathy associated with anti‐MAG antibodies

Abstract: No causative or curative therapy exists for the polyneuropathy associated with antibodies to myelin-associated glycoprotein (anti-MAG). Rituximab is a mouse-human chimeric antibody that specifically eliminates B-cells and B-cell precursors. Preliminary results suggest a beneficial effect on antibody-dependent autoimmune diseases. Nine patients with an anti-MAG-associated IgM polyneuropathy received rituximab once weekly for 4 weeks. In all patients, the number of B-cells in the peripheral blood declined below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
1
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(109 citation statements)
references
References 17 publications
5
97
1
6
Order By: Relevance
“…Our results confirmed the median change in B-cell and CD20 cell counts reported in previous studies, 14,15,18 but it is unclear whether this reflects the beneficial effect of rituximab in IgM anti-MAG demyelinating neuropathy. It would be important to determine levels of B-cell-activating factor (BAFF), which controls B-cell homeostasis, to further understand the role of these cells in treatment.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Our results confirmed the median change in B-cell and CD20 cell counts reported in previous studies, 14,15,18 but it is unclear whether this reflects the beneficial effect of rituximab in IgM anti-MAG demyelinating neuropathy. It would be important to determine levels of B-cell-activating factor (BAFF), which controls B-cell homeostasis, to further understand the role of these cells in treatment.…”
supporting
confidence: 90%
“…12,13 Rituximab is a genetically engineered chimeric murine/human monoclonal antibody directed against CD20, a protein present on the surface of normal and malignant pre-B and mature B cells until differentiation into plasma cells. Efficacy of rituximab has been supported by both uncontrolled studies [14][15][16][17] and, more recently, an RCT that concluded there was a small difference between rituximab and placebo-treated patients, 18 although confirmation is needed in a larger trial. The aim of the Rituximab vs Placebo in Polyneuropathy Associated With Anti-MAG IgM Monoclonal Gammopathy (RIMAG) study was to test the hypothesis that rituximab at 375 mg/m 2 is beneficial in patients with IgM anti-MAG demyelinating neuropathy.…”
mentioning
confidence: 99%
“…On the basis of these results, Rituximab was approved in 2006 for use in RA patients who do not respond to TNF-antagonists (Sabahi and Anolik, 2006). Rituximab has also shown benefit in several other autoimmune diseases, including autoantibody-associated neuropathies, immune thrombocytopenia and systemic lupus erythematosus (Edwards and Cambridge, 2006;Renaud et al, 2003Renaud et al, , 2006Sabahi and Anolik, 2006;Tanaka et al, 2007).…”
Section: Therapeutic Depletion Of B Cells In Ms With Rituximabmentioning
confidence: 99%
“…55,56 In a phase II, 12-month pilot study, nine patients with anti-MAG neuropathy who were resistant to other therapies were treated with rituximab 375 mg/m 2 . 57 This study demonstrated clinical improvement in six of the nine patients by at least 2 points on the neurological disability score, and seven had improved nerve conduction studies by at least 10%. There was laboratory evidence of reduction of B cells, anti-MAG antibodies, and total IgM.…”
Section: Therapy Of Anti-myelin-associated Glycoprotein Polyneuropathymentioning
confidence: 52%